NOODWER EXSES YANG DILAKUKAN OLEH KORBAN TINDAK PIDANA KEKERASAN SEKSUAL YANG MENGAKIBATKAN PELAKU MENGALAMI CACAT PERMANEN - Putri Pradini, Norin (UIR Press, 2025)
The defense of being forced to go beyond limits is a defense that exceeds the limits of a person's ability to defend themselves when they experience a sudden attack in an emergency situation due to the emotional turmoil caused by the attack.The research questions addressed in this paper include how to provide legal protection for victims of sexual violence who commit excessive force resulting in permanent disability and the legal responsibilities of victims who commit excessive force resulting in permanent disability.The research method employed in this thesis is a normative research method, employing both a legislative and a conceptual approach. Several legal sources, including primary and secondary legal sources, were used. The legal sources were reviewed through a literature review, reviewing existing legislation and literature.In criminal law regarding excessive self-defense (Noodwer Exses) in accordance with Article 49 paragraph 2 of the Criminal Code, namely excessive self-defense is given the right to carry out a defense where this defense aims to protect one's own honor or even that of others. Criminal liability in the context of Noodwer Exses, in this case the victim who carries out the defense inadvertently resists, so that his actions are justified by the Law due to the mental shock experienced by the victim who carries out the defense. Keywords: Noodwer Exses, Crime of sexual violence, Permanent Disability.